Class C CpG Oligodeoxynucleotide Immunomodulatory Response in Aged Squirrel Monkey (Saimiri Boliviensis Boliviensis) - Nehete, Pramod N.; Williams, Lawrence E.; Chitta, Sriram; Nehete, Bharti P.; Patel, Akash G.; Ramani, Margish D.; Wisniewski, Thomas; Scholtzova, Henrieta (Frontiers in Aging Neuroscience, 2020)
One means of stimulating the mammalian innate immune system is via Toll-like receptor 9 (TLR9) being exposed to unmethylated cytosine-phosphate-guanine (CpG) DNA, also known as pathogen-associated molecular patterns of microbial origin. Synthetic CpG oligodeoxynucleotides (ODNs) with defined CpG motifs possess broad immunostimulatory properties that make CpG ODNs suitable as therapeutic interventions in a variety of human disease conditions, including Alzheimer’s disease (AD). Rodent models are often used for preclinical testing of the effectiveness of CpG ODN therapeutic agents for AD and other disorders. However, the translatability of findings in such models is limited due to the significant difference of the distribution of TLR9 between primates and rodents. The squirrel monkey (SQM), a well-established New World non-human primate (NHP), is known to be phylogenetically proximate to humans and develops extensive age-dependent cerebral amyloid angiopathy (CAA), a key pathological feature of AD. Hence, this model is currently being used to test AD therapeutics. In the present study, we conducted the first examination of Class C CpG ODN’s immunomodulatory role in elderly SQMs. We documented the effectiveness of CpG ODN to trigger an immune response in an aged cohort whose immune system is senescent. The specific immune response patterns detected here, closely resembled CpG ODN-induced immunostimulatory patterns observed in prior human studies. Overall, our findings provide critical data regarding the immunomodulatory potential of CpG ODN in this NHP model allowing for future therapeutic trials of innate immunity stimulation via TLR9 agonists for diverse indications including AD therapeutics.